Art and Challenges Involved in the Treatment of Ischaemic Damage - Saiz-Sapena, Nieves; Aparici-Robles, Fernando; Tsoulfas, Georgios (IntechOpen, 2022)
This edited volume Art and Challenges Involved in the Treatment of Ischemic Damage is a collection of reviewed and relevant research chapters, offering a comprehensive overview of recent developments in this specific field. The book comprises single chapters authored by various researchers and edited by an expert active in the research area. All chapters are complete in themselves but united under a common research study topic. This publication aims at providing a thorough overview of the latest research efforts by international authors and experts in the field of study and at opening new possible research paths for further novel developments.